2021
DOI: 10.1038/s41598-021-01174-w
|View full text |Cite
|
Sign up to set email alerts
|

Trends, relationships and case attribution of antibiotic resistance between children and environmental sources in rural India

Abstract: Bacterial antibiotic resistance is an important global health threat and the interfaces of antibiotic resistance between humans, animals and the environment are complex. We aimed to determine the associations and overtime trends of antibiotic resistance between humans, animals and water sources from the same area and time and estimate attribution of the other sources to cases of human antibiotic resistance. A total of 125 children (aged 1–3 years old) had stool samples analysed for antibiotic-resistant bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Twenty-four studies were designed in the context of specific countries [ 22 44 ], and four were sub-national [ 45 48 ]. Most national and sub-national studies were conducted in North American and European countries, but three studies originated from SSEA countries [ 35 , 46 , 47 ]. The highest number (10) of national study publications were from the United States [ 11 , 25 29 , 32 , 38 , 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-four studies were designed in the context of specific countries [ 22 44 ], and four were sub-national [ 45 48 ]. Most national and sub-national studies were conducted in North American and European countries, but three studies originated from SSEA countries [ 35 , 46 , 47 ]. The highest number (10) of national study publications were from the United States [ 11 , 25 29 , 32 , 38 , 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The articles were published over a range of nearly 40 years, mainly as a consequence of a 1984 investigation of resistant salmonellosis outbreaks in the United States [ 29 ]. However, most studies (87%) were published between 2012 and 2022, and 12 have been published since 2020 [ 19 , 21 , 22 , 25 , 30 , 34 , 35 , 38 40 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overuse and misuse of antimicrobials are important drivers of AMR, however, antimicrobial consumption alone does not explain the variations in AMR. 41 Therefore, other factors in the environment need considering from One Health perspectives such as the presence and AMU of co-existing animals, occupation, diet, health, sanitation, and cultural traditions. 42 A recent study showed that the association between AMU and AMR was more apparent for populations with higher hygiene levels.…”
Section: Discussionmentioning
confidence: 99%